2016
DOI: 10.3126/jbmr.v1i1.14547
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of Workplace Spirituality Scale in an Eastern Context

Abstract: Several scales for measuring workplace spirituality (WPS) are available. However, a majority of the available scales were developed in the Western context that may not be generalizable in an Eastern context. Petchsawang and Duchon (2009) developed a 22-item, four dimensional WPS scale with a sample from an Eastern Buddhist-centric culture for capturing WPS in an Eastern context. The purpose of this study was to assess the generalizability, dimensionality, and convergent and discriminant validity of this scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Hence, it was concluded that discriminant validity was also established between the constructs. These findings have some inconsistencies with the findings of Shrestha (2016), who found that the internal consistency reliability of compassion dimension was below .70 and discriminant and convergent validity of transcendence dimension did not meet all measures to ensure validity.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Hence, it was concluded that discriminant validity was also established between the constructs. These findings have some inconsistencies with the findings of Shrestha (2016), who found that the internal consistency reliability of compassion dimension was below .70 and discriminant and convergent validity of transcendence dimension did not meet all measures to ensure validity.…”
Section: Discussioncontrasting
confidence: 95%
“…Associations between each statement and its dimension ranged from 0.34 to 0.81, and the r-square from 0.12 to 0.71, which provided proof of satisfactory convergent validity of WPS in the South Asian context. Shrestha (2016) validate this scale in the Nepali context who found that the internal consistency reliability of the compassion dimension was below .70 and discriminant and convergent validity of transcendence dimension did not meet all the criteria to confirm the validity of this scale.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Workplace spirituality is how a person interprets and lives his religious values and then applies them to the workplace environment so that they can work well to improve performance and establish good relationships with others at work. Shrestha (2016) Workplace spirituality defines workplace spirituality as an organizational value framework reflected in a culture that encourages employees to experience transcendental experiences through work processes so that they feel connected to others thoroughly and happily. According to Shrestha (2016), Mindfulness, transcendence, purposeful labor, and compassion are aspects of spirituality in the workplace.…”
Section: Spirituality In the Workplacementioning
confidence: 99%
“…Shrestha's (2016) validation study found support for validity and reliability of this scale. Present findings also provide additional validity support for this scale.…”
Section: Theoretical Implicationsmentioning
confidence: 99%